Prevalence and Distribution of Anemia Risk Factor in Patient with Chronic Hepatitis C who Has Combination therapy of Interferon Alpha and Ribavirin - Femmy Nurul Akbar; Zuljasri Albar; Abdul Muthalib; Laurentius Lesmana; Nurul Akbar (The Indonesian Society for Digestive Endoscopy, 2006)
Background: Interferon alfa and ribavirin combination therapy is one of effective standard therapy for chronic hepatitis C (CHC.) However, anemia is a common side effect of this therapy that patients have to reduce or discontinue ribavirin therapy. But ribavirin dose reduction or discontinuation can reduce the effectivity of the therapy. Hence, it is important to know the prevalence of anemia and to determine the factors associated with anemia. Objective: To know the prevalence of anemia and some risk factors associated with anemia caused by the combination therapy in chronic hepatitis C. Method: Sixty one of CHC patients who received combination therapy were included in this study. The study used cross sectional design and data were obtained by measured complete blood count on 8th week of therapy. Result: Subjects 47 (77%) were males, 14 (23%) were females with mean age 38.9 years. Subjects had genotype 1 and 4 were 23 (71.9%) and 44 (72.1%) subjects received 1,000 mg ribavirin. Prevalence of anemia was found to be 52.5%. On multivariate analysis, only pretreatment hemoglobin concentration 14 g/dl was found to be the risk factor of anemia. Conclusion: Prevalence of anemia was 52.5%. Pretreatment hemoglobin concentration 14 g/dl was only found to be the risk factors of anemia. Although age 50 years or female were not found to be the risk factor of anemia but patient with these risk factors should be carefully monitored. Intervention to prevent anemia should be considered to these patients. Eight subjects from 32 anemia patients had ribavirin dose reduction, and no patient had discontinuation treatment on 8th week of therapy. Keywords: chronic hepatitis C, IFN-alfa- RIB combination therapy, risk factors of anemia